Correction to: Investigation of Liquefaction in Balaroa, Petobo, and Jonooge (Central Sulawesi, Indonesia) Caused by the 2018 Palu Earthquake Sequence - Triyono, Rahmat; Widiyantoro, Sri; Zulfakriza, Zulfakriza; Supendi, Pepen; Rahman, Aditya Setyo; Gunawan, Mohamad Taufik; Oktavia, Nur Hidayati; Rahmatullah, Fajri Syukur; Fadhilah, Fildzah Zaniati; Habibah, Nur Fani; Sativa, Oriza; Permana, Dadang; Wallansha, Robby; Octantyo, Ardian Yudhi; Persada, Yoga Dharma; Pranata, Bayu; Sujabar, Sujabar (Journal of Engineering and Technological Sciences, 2025)
Correction to:  Journal of Engineering and Technological Sciences https://doi.org/10.5614/j.eng.technol.sci.2024.56.3.1   The article titled "Investigation of Liquefaction in Balaroa, Petobo, and Jonooge (Central Sulawesi, Indonesia) Caused by the 2018 Palu Earthquake Sequence" , written by Rahmat Triyono, Sri Widiyantoro, Zulfakriza, Pepen Supendi, Aditya Setyo Rahman, Mohamad Taufik Gunawan, Nur Hidayati Oktavia, Fajri Syukur Rahmatullah,Fildzah Zaniati Fadhilah, Nur Fani Habibah, Oriza Sativa, Dadang Permana, Robby Wallansha, Ardian Yudhi Octantyo, Yoga Dharma Persada, Bayu Pranata, and Sujabar, was originally published electronically on thepublisher’s internet portal on 19 June 2024 . The corresponding author's affiliation at the time of publication was as follows: (1) Indonesian Agency of Meteorology, Climatology, and Geophysics, Jalan Angkasa 1 No. 2, Jakarta 10610, Indonesia; and (2) Global Geophysics Research Group, Faculty of Mining and Petroleum Engineering, Institut Teknologi Bandung, Jalan Ganesa No. 10, Bandung 40132, Indonesia.   Subsequently, the authors decided to update the corresponding author's affiliation to: (1) Geophysical Engineering Graduate Program, Faculty of Mining and Petroleum Engineering, Institut Teknologi Bandung, Jalan Ganesa No. 10, Bandung 40132, Indonesia; and (2) Indonesian Agency of Meteorology, Climatology, and Geophysics, Jalan Angkasa 1 No. 2, Jakarta 10610, Indonesia.   The original article can be found online at https://doi.org/10.5614/j.eng.technol.sci.2024.56.3.1